Ability of (extruded) pea protein products to partially replace pork meat in emulsified cooked sausages. (June 2022) - Broucke, Keshia; Van Poucke, Christof; Duquenne, Barbara; De Witte, Bavo; Baune, Marie-Christin; Lammers, Volker; Terjung, Nino; Ebert, Sandra; Gibis, Monika; Weiss, Jochen; Van Royen, Geert
Abstract: The effect of replacing 20% pork meat in cooked sausages by Pea Protein Isolate (PPI), pea Low Moisture Extrudates (LME), and pea High Moisture Extrudate (HME) on the nutritional, techno-functional and sensorial properties of emulsified cooked sausages was investigated. All hybrid sausages contained all essential amino acids in sufficient amounts. Interestingly, extrusion significantly reduced the Anti-Nutritional Factors (ANF) trypsin and chymotrypsin inhibitors, and the allergenic pea Pis s2 (convicilin) content. Inclusion of (texturized) pea proteins into hybrid meat sausages resulted in weaker networks, and thus (significant) softer bite, and significant color changes. The expert taste panel did not note any significant differences between the hybrid sausage with PPI and its reference for all sensorial attributes. Industrial relevance: Producing meat substitutes with powdered or extruded plant-based protein products, such as PPI, LME, and HME, can result in several limitations concerning textural, nutritional and sensorial features. To avoid these hurdles, hybrid meat products, where a fraction of the meat is replaced by alternative proteins, may bring a solution. This work demonstrated that 20% of pork meat can be replaced by pea products PPI, LME or HME in emulsified cooked sausages without any implications towards the amino acid profile. Moreover, using extruded pea products could even significantly reduce ANF trypsin and chymotrypsin inhibitors and the allergenic pea convicilin contents. This knowledge plays a crucial role for product development, as this demonstrates that hybrid meats can be produced with great nutritional qualities. The challenges identified were that the hybrid sausage exhibited a weaker network with softer texture, and the inclusion of extruded proteins led to large cavities with jelly-like excretion. This demonstrates the importance of selecting suitable (forms of) plant proteins for the production of hybrid meats with great techno-functional and organoleptic properties. Highlights: Hybrid meat formulations with complete amino acid profile were obtained. Extrusion improved nutritional quality by reducing ANF and pea allergen content. Including pea proteins in hybrid meat matrix weakened network formation. Using PPI in hybrid meats did not significantly alter sensorial traits.